Chitosan-DNA nanoparticles: The effect of cell type and hydrolysis of chitosan on in vitro DNA transfection - TURAN, KADİR (TAYLOR & FRANCIS INC, 2006)
Commercial chitosan (Ch) with low (LMWCh) and medium molecular weight (MMWCh) were hydrolyzed in diluted hydrochloric acid by heating at different temperatures. The viscosity average molecular weight of Chs was gradually decreased from 450 to 14 kDa as a function of temperature. Ch fractions were used for formation of Ch-DNA nanoparticles and tested for the ability to introduce DNA into HEK293, Swiss3T3, HeLa, and MDCK cells in vitro. The average diameter of nanoparticles was 200-220 nm. The surface charge of nanoparticles varied depending on the Ch/DNA ratio. The cell lines different response to DNA transection with Ch fractions depended on molecular weight. HEK293 cells were efficiently transfected by nanoparticles prepared with Chs having a wide range of molecular weight (similar to 14-195 kDa). Swiss3T3 cells were efficiently transfected by Ch polymers with about <17 kDa. In contrast, HeLa and MDCK cells were highly resistant to DNA transfection with Ch polymers. These results strongly suggest that Ch polymers may be widely used for DNA trasnfection of the mammalian cells under optimized conditions.
Keywords: chitosan; nanoparticles; gene delivery; nonviral; chitosan-DNA complexes; GENE-TRANSFER; MAMMALIAN-CELLS; MOLECULAR-MASS; DELIVERY; COMPLEXES; EFFICIENCY; SERUM; MICROPARTICLES; MECHANISM; LIPOSOME